Pornography and sexual aggression in adult males - Daniels, Sophie (2020)
Overall, this thesis explored the impact of viewing pornography on adult males, particularly on attitudes towards sexual aggression including rape myth acceptance. The systematic review served to provide a starting point and reviewed the impact of exposure to pornography on attitudes towards sexual aggression; typically, acceptance of rape myths and attitudes towards sexual coercion. A narrative synthesis generally suggested that exposure to pornography, particularly pornography inclusive of violent themes, has detrimental effects on males attitudes towards sexual aggression.